Investigating Job Satisfaction Among Emergency Department Workers In A Private Hospital During The Pandemic - Caroline Ratnasari; Jacob Donald Tan (Syntax Corporation, 2022)
In Indonesia during the COVID-19 pandemic situation, there is a surge of health care demand that leads to exhaustion and resignation of health workers. The emergency department plays an important role in providing care in Surya hospital, but many factors due to the unpredictable nature of the emergency department influence health workers’ satisfaction. Managing job satisfaction is essential as it increases the commitment and human capital potential of an employee, which subsequently contributes to the quality of care provided to the patients. This research investigates job satisfaction among health workers in the emergency department of Surya Hospital. In-depth semi-structured interviews and direct observations were employed in the study. From this study synergized teamwork increases emergency workers’ job satisfaction. On the other hand, complex recruitment processes, lack of compensation and benefits policy, and ineffective communication flow decrease job satisfaction. This research could guide the mediation between health workers and hospital management in providing a better working environment in the emergency department